Decomposing the Spatial and Temporal Effects of Climate and Habitat on a Hazel Grouse (Tetrastes bonasia) Population in Northeastern Chinese Mountains - Xiaoying Xing; Yuesen Zhang; Xiang Li; Guangshun Jiang (Animals, 2023)
Habitat, climate, and human disturbances have important effects on wildlife, and these are especially critical for threatened species. In this study, we used infrared camera traps to monitor the population dynamics of the hazel grouse (Tetrastes bonasia) from 2012 to 2021 in northeast China and explore the effects of habitat, climate, and human disturbance on their distribution. We analyzed 16 environmental variables related to significant differences between presence recordings and absence recordings within and between seasons. Temperatures and roads influenced the distribution of the hazel grouse, but topography and vegetation types did not. The hazel grouse preferred deciduous forest and oak forest from spring to autumn. This study provides ecological information to help guide the mountain habitat management of the hazel grouse in national parks.